BIOSAFETY IN DENTISTRY IN TIMES OF COVID-19: REVIEW - Valois Miranda, André Lucas (2022)
Biosafety protocols in Dentistry are constantly being modified and improved, as research is carried out. Due to the COVID-19 pandemic, questions arose about the continuity of dental practice. The main objective of this literature review is to describe different Biosafety protocols in Dentistry adopted during the COVID-19 pandemic. The bibliographic search was performed in the PubMed and Google Scholar databases, using the terms: dental practice AND (biosafety OR COVID-19); COVID-19 vaccine AND dentistry; masks AND COVID-19 AND dentistry; personal protective equipment AND COVID-19 AND dentistry; mouthwash AND COVID-19 AND dentistry; disinfection materials AND COVID-19 AND dentistry. The results showed that many changes in Biosafety protocols would be necessary and that there is agreement among the authors about them. The careful follow-up of the protocols would be the best way for the dentist to contribute to the control of the COVID-19 pandemic